Seeded Growth Route to Noble Calcium Carbonate Nanocrystal. - Aminul Islam; Siow Hwa Teo; M Aminur Rahman; Yun Hin Taufiq-Yap (PLoS ONE, 2015)
A solution-phase route has been considered as the most promising route to synthesize noble nanostructures. A majority of their synthesis approaches of calcium carbonate (CaCO3) are based on either using fungi or the CO2 bubbling methods. Here, we approached the preparation of nano-precipitated calcium carbonate single crystal from salmacis sphaeroides in the presence of zwitterionic or cationic biosurfactants without external source of CO2. The calcium carbonate crystals were rhombohedron structure and regularly shaped with side dimension ranging from 33-41 nm. The high degree of morphological control of CaCO3 nanocrystals suggested that surfactants are capable of strongly interacting with the CaCO3 surface and control the nucleation and growth direction of calcium carbonate nanocrystals. Finally, the mechanism of formation of nanocrystals in light of proposed routes was also discussed.